Diffusion indicator for hemispheroidal and ring ultramicroelectrode geometries for E and ECʹ reactions - R. Usha Rani; L. Rajendran (Electrochemistry Communications, 2021)
The diffusion indicator α described by Haonan and Compton (Journal of Electroanalytical Chemistry, 866 (2020) 114149) is derived for hemispheroidal and ring microelectrodes. The diffusion associated with six electrodes of various geometries (microsphere, microdisc, oblate, prolate, whisker and ring) is studied using this general diffusion indicator parameter. The general parameter α is obtained from theoretical and empirical chronoamperometric current equations for E and EC′ reactions in the literature. In the various geometries, the value of the diffusion indicator and its evolution over time demonstrate the contrasting influences of planar and convergent/divergent diffusion.